Congenital Diaphragmatic Hernia: State of the Art in Translating Experimental Research to the Bedside - Antounians, Lina; Figueira, Rebeca Lopes; Sbragia, Lourenço; Zani, Augusto (European Journal of Pediatric Surgery, 2019)
Congenital diaphragmatic hernia (CDH) is a devastating disease that still carries a high mortality and morbidity rate. Poor outcomes for fetuses and infants with CDH are mainly related to pulmonary hypoplasia (PH) and pulmonary vascular remodeling that leads to pulmonary hypertension (PHTN). Over the last five decades, research efforts have focused on modeling CDH not only to study the pathophysiology of the diaphragmatic defect, pulmonary hypoplasia, and pulmonary hypertension, but also to identify therapies that would promote lung growth and maturation, and correct vascular remodeling. As CDH is a multifactorial condition whose etiology remains unknown, there is not a single model of CDH, rather several ones that replicate different aspects of this disease. While small animals like the mouse and the rat have mainly been used to uncover biological pathways underlying the diaphragmatic defect and poor lung growth, larger animals like the lamb and the rabbit models have been instrumental for pursuing medical and surgical interventions. Overall, the use of animal models has indeed advanced our knowledge on CDH and helped us test innovative therapeutic options. For example, the lamb model of CDH has been the paradigm for testing fetal surgical procedures, including tracheal occlusion, which has been translated to clinical use. In this review, we outline the induction protocols of CDH in animals with the use of chemicals, dietary changes, genetic alterations, and surgical maneuvers, and we describe the studies that have translated experimental results to the bedside.
Keywords: congenital diaphragmatic hernia; pulmonary hypoplasia; lung development; fetal surgery; FETO